PENGARUH FAKTOR KEUANGAN DAN NON KEUANGAN TERHADAP OPINI GOING CONCERN (Studi Empiris Perusahaan Manufaktur di BEI Tahun 2006 – 2010) (Students' Journal of Accounting and Banking, 2012)
The purpose of this research was to test and analyze the effect of audit quality, debt default, the financial condition of the company, and the company’s growth to the audit opinion going concern on the manufacturing company that went public in Indonesia. The population in this research is the company specializing in the manufacturing sector are listed on the Indonesia stock exchange (idx) for 2006-2010. Sampling techniques using a purposive sampling technique.  The sample in this study as much as 70 sample company consisting of 44 samples received an audit opinion going concern, sample received an audit opinion 26 non going concern. The result showed that the quality of audit and the company’s growth is not significant to the issuance of the audit opinion going concern. Debt default and the the company’s financial condition to the issuance of audit opinions are significant going concern. Keywords: Quality Audit, Debt default, The Financial Condition of the Company, The Company’s Growth, and Going Concern Audit Opinion.